A comprehensive checklist of earthworm species and subspecies from Vietnam (Annelida: Clitellata: Oligochaeta: Almidae, Eudrilidae, Glossoscolecidae, Lumbricidae, Megascolecidae, Moniligastridae, Ocnerodrilidae, Octochaetidae) - Nguyen, Tung T.; Nguyen, Anh D.; Tran, Binh T.t.; Blakemore, Robert J. (Zootaxa, 2016)
The comprehensive checklist of earthworms in Vietnam is presented here listing 24 genera and 212 species arranged in eight families. For each species, bibliographic citations are given, including the original descriptions as well as notable citations affecting taxonomic status or distributional reports of a species. Distributions of each species are also provided. The bibliography contains all relevant papers for Vietnamese earthworms. Of 212 species, 114 have been recorded only in Vietnam, and 25 are cosmopolitan. New combinations are made for Amynthas acalifornicus (Do & Huynh, 1991) comb. nov., A. binhgiaensis (Le, 1994) comb. nov., Metaphire catbaensis (Thai & Le, 1993) comb. nov., M. khoii (Do & Tran, 1994) comb. nov., M. phaluongana (Do & Huynh, 1992) comb. nov., and M. mangophila (Nguyen, 2011) comb. nov., M. tripidoporophoratus (Thai & Nguyen, 1993) comb. nov. Additionally, Pheretima paraalexandri Nguyen, 2011 is treated as a junior synonym of Amynthas polychaetiferus (Thai, 1984).